Isolation and characterization of a covalent CeIV-Aryl complex with an anomalous 13C chemical shift - Grace B. Panetti (Nature Portfolio, 2021)
Ce(IV) organometallic compounds are rare due to Ce(IV) being a powerful oxidant. Herein, the authors explore the covalency of a pair of organocerium complexes bearing a Ce(IV)-C(aryl) bond and examine their structure by NMR spectroscopy, X-ray diffraction analysis, and computational calculations.